New species discovered from old collections, the case of Hedysarum wangii sp. nov. (Fabaceae, Hedysareae) - Liu, Pei-Liang; Chen, Xue-Lin; Lu, Yuan; Chang, Zhao-Yang; Yue, Ming (Phytotaxa, 2019)
Hedysarum wangii sp. nov. (Fabaceae) is described and illustrated based on historical collections, field observations and molecular phylogenetic analysis. The new species is similar to H. minjanense and H. lehmannianum, but can be diagnosed by details of its leaves, flowers and fruit. Phylogenetic trees based on nuclear ETS, ITS and plastid psbA-trnH, trnL-F, trnS-G and petN-psbM sequences indicated that H. wangii is a member of sect. Stracheya, and is closely related to H. minjanense. A key to species in sect. Stracheya is provided. Initiated by a specimen collected in the year 1937, the discovery of H. wangii highlights the importance of historical herbarium collections in our understanding of species diversity.